2013
DOI: 10.1186/1742-4690-10-81
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 capsid undergoes coupled binding and isomerization by the nuclear pore protein NUP358

Abstract: BackgroundLentiviruses such as HIV-1 can be distinguished from other retroviruses by the cyclophilin A-binding loop in their capsid and their ability to infect non-dividing cells. Infection of non-dividing cells requires transport through the nuclear pore but how this is mediated is unknown.ResultsHere we present the crystal structure of the N-terminal capsid domain of HIV-1 in complex with the cyclophilin domain of nuclear pore protein NUP358. The structure reveals that HIV-1 is positioned to allow single-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 65 publications
5
107
0
1
Order By: Relevance
“…31). It was recently reported that the cyclophilin domain of Nup358 is an isomerase that catalyzes cistrans isomerization of a proline in HIV-1 CA (P90), which facilitates viral core uncoating and nuclear import of PICs (32). We hypothesize that the CA stability mutants directly or indirectly interfere with the CA-Nup358 interaction, or interaction of the CA with another NE associated protein, which reduce association of the PICs with the NE and diminish nuclear import.…”
Section: Discussionmentioning
confidence: 95%
“…31). It was recently reported that the cyclophilin domain of Nup358 is an isomerase that catalyzes cistrans isomerization of a proline in HIV-1 CA (P90), which facilitates viral core uncoating and nuclear import of PICs (32). We hypothesize that the CA stability mutants directly or indirectly interfere with the CA-Nup358 interaction, or interaction of the CA with another NE associated protein, which reduce association of the PICs with the NE and diminish nuclear import.…”
Section: Discussionmentioning
confidence: 95%
“…It is noteworthy that CPSF6 and NUP153 not only appear to function in the same nuclear import pathway but also share the same CA binding site. This is reminiscent of CypA and NUP358, which similarly compete for binding [16]. Whether this reflects a sequential pathway, with CypA and CPSF6 operating upstream of NUP358 and NUP153, and what the purpose of this might be, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…18 and 19). The cis-trans isomerization is catalyzed by CypA and Nup358Cyp (18,19). The uncatalyzed reaction is slow (exchange rates of <0.1 s −1 ), whereas in the presence of CypA and NUP358Cyp, isomerization rates of 6.6 and 12.1 s −1 were observed, respectively.…”
Section: Significancementioning
confidence: 99%